Real time observation of proteolysis with Fourier transform infrared (FT-IR) and UV-circular dichroism spectroscopy: Watching a protease eat a protein - Vorob'ev, Mikhail M.; Vogel, Vitali; Džafić, Enela; Mäntele, Werner; Güler, Günnur (Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 2011)
Fourier transform infrared (FT-IR)- and UV-circular dichroism (UV-CD) spectroscopy have been used to study real-time proteolytic digestion of β-lactoglobulin (β-LG) and β-casein (β-CN) by trypsin at various substrate/enzyme ratios in D(2)O-buffer at 37°C. Both techniques confirm that protein substrate looses its secondary structure upon conversion to the peptide fragments. This perturbation alters the backbone of the protein chain resulting in conformational changes and degrading of the intact protein. Precisely, the most significant spectral changes which arise from digestion take place in the amide I and amide II regions. The FT-IR spectra for the degraded β-LG show a decrease around 1634 cm(-1), suggesting a decrease of β-sheet structure in the course of hydrolysis. Similarly, the intensity around the 1654 cm(-1) band decreases for β-CN digested by trypsin, indicating a reduction in the α-helical part. On the other hand, the intensity around ∼1594 cm(-1) and ∼1406 cm(-1) increases upon enzymatic breakdown of both substrates, suggesting an increase in the antisymmetric and symmetric stretching modes of free carboxylates, respectively, as released digestion products. Observation of further H/D exchange in the course of digestion manifests the structural opening of the buried groups and accessibility to the core of the substrate. On the basis of the UV-CD spectra recorded for β-LG and β-CN digested by trypsin, the unordered structure increases concomitant with a decrease in the remaining structure, thus, revealing breakdown of the intact protein into smaller fragments. This model study in a closed reaction system may serve as a basis for the much more complex digestion processes in an open reaction system such as the stomach.